(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2016)
Background: Having achieved delivery of cooked food in all states and reaching out to children (6-14 yrs) through centralized and decentralized delivery model Mid Day Meal scheme has not been able to achieve its own mandate of providing nutrition. Many studies have attributed gaps in delivery to lack of awareness and trained human resource in preparation of cooked meals. Objectives: A pilot study was undertaken in two blocks of Faizabad district with an objective of providing interventions in area of human resource development and community participation. Methodology: Through baseline survey (n= 70 schools) in two blocks, issues in delivery were studied and provided specific interventions. Results: Baseline survey established the fact that quantities consumed by the child do not provide prescribed nutrition. Menu was standardized for amounts and standard Operating Procedures (SOPs). Pictorial training manual was developed to train master trainers as well as cooks. Location specific training using local idiom was used and campaign was conducted to enhance community participation in 45 villages. Conclusion: Accomplishing comprehensive improvement without proper human resource policy is a challenge especially in rural areas. Developed Standard Operating Procedures (SOPs), awareness and capacity building through campaigns and training had positive impact on delivery of nutrition.